Antecedents of the Accounting Profession. - Stone, Williard E. (The Accounting Review, 1969)
Abstract Auditing undoubtedly appeared shortly after man began to record governmental and commercial transactions for you have evidence that even the earliest records were audited. The first attempts to reduce transactions to some medium more permanent than memory probably took a semi-mechanical form. Man probably began a more formal recording of transactions in the dim past when trade between tribes increased. At first, pictures of the objects traded may have been used but by 5,000 B.C. symbols, mutually intelligible to tribes of diverse languages, had been developed. An early Mesopotamian civilization, the Sumerian, recorded commercial transactions on stone dating back to 3,600 B.C. and on day tablets beginning about 3,200 B.C. It is here that the auditor first gives concrete evidence of his existence and that you find the first examples of internal control. In ancient Egypt in the Pharaoh's central finance department, the "house of silver of the treasury," internal control and auditing were In use. Scribes prepared records of receipts and disbursements of silver, corn and other commodities. One recorded on papyrus the amount brought to the warehouse and another checked the emptying of the containers on the roof as It was poured into the storage building.